The Employment of Rhetorical Strategies in Writing Literary Criticism: An Introduction for College Freshman - Ballard, Brandi L. (URJ-UCCS: Undergraduate Research Journal at UCCS, 2011)
As a field of study, literary criticism is open to the constant review and reinterpretation of accepted literary works. Although new interpretations are welcome, the audience must be convinced of the value and validity of these ideas. As an introduction for college freshman, this article explores the formation of arguments in the field of literary criticism through the use of rhetoric. By understanding the commonplaces of the academic literary community, using the stasis of conjecture, and providing evidence, a rhetor is able to effectively construct a literary argument.